(3GdJHjGf dHOjYI GdHjGfs - (3TeS GdOjf CHi YHO Gddg eMeO Hf CHi HcQ YHO Gddg Hf eMeO Hf CMeO Hf fGUQ GdOjf GdbjSi GdTGaYjs
(3ChdgG (B:s
(3GdMeO ddg Ydi eG TQM ef GdUOhQ dESdGe s
(3BNQgG (B:s
(3aQGZ GdTQM ddbUjOI hGdcdGe , hjSCd Gddg YR hLd UdGM GdMGd hMSf GdYGajg hGdeBd s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B3 - (3U (B91 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs